Practical Approach to Peripheral Arterial Chronic Total Occlusions - Banerjee, Subhash (Springer Singapore : Imprint: Springer, 2017)
A practical, highly illustrative and easy to read reference for interventional cardiologists, vascular surgeons, cardiac/endovascular catheterization laboratory personnel, interventional radiologists, technical staff, industry professionals, investigators, and researchers on peripheral arterial CTO interventions. Peripheral CTO lesions are present in nearly 50% of all peripheral arterial disease (PAD) endovascular interventions. There is tremendous growth in the performance and learning of peripheral arterial CTO procedures. There are several ongoing physician courses and many others that are being prepared; however, there is a significant lack of standardized selection, strategies, techniques and equipment necessary to achieve a high degree of reproducible success with low complication rates during the performance of these complex and technically challenging endovascular procedures. The book is not an academic "tour de force" description of the topic but rather a practical one with many illustrations and step-by-step explanations of the various procedure steps, what can go wrong, and troubleshooting. Heavy use of illustrations throughout limit the text to what is necessary to convey the message, and the book is supported by online case catalogues and board review questions. The book also includes never-before-published information on new technology.
Keywords: Medicine.; Interventional radiology.; Angiology.; Cardiology.; Vascular surgery.; elektronické knihy; electronic books